Blended learning in training courses for universitycontent teachers; 10th International Technology, Education and Development Conference (INTED2016), Valencia, Spain, 7-9 March, 2016 - Slesarenko I. V. Inga Valerievna; Zabrodina I. K. Irina Konstantinovna; Netesova M. V. Mariya Vitalevna; Tran Din Tan Sy; Page M. Mary (2016, 2016)
Title screen